Topografia e densidade da madeira modulam o crescimento sazonal na Amazônia Central - Melgaço, Karina Liana Lisboa (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
Global climatic changes are widely recognized as the greatest current environmental impact, but the effects and mechanisms by which climate affects the carbon balance of tropical forests are uncertain. Growth seasonality has been studied in an attempt to understand this. Here we investigated how hydro-topographic gradients and wood density modulate intra-annual growth of trees in a terra-firme forest in central Amazonian Brazil. A total of 1,879 trees and palms were monitored with dendrometers every two months in nine 1ha plots. Growth varied as a function of terrain height above the nearest drainage, soil texture and wood specific gravity across time. Increases in girth were mostly associated with raising rainfall during the transition from dry to wet season. At the end of the wet season, trees in clayey soils and vertically far from the water table had greater growth increments than trees in slopes and sandy valleys. However, at the start of the dry season, higher growth rates occurred in valleys and slopes with sandy soils. Additionally, trees with high specific gravity woods maintained low intra-annual girth growth variability, with increment increases in the transition period from dry to wet season, while trees with low specific gravity woods had a broad range of growth variability. These differences suggest that a trade-off between wood growth investment and hydraulic safety may be driving physiological responses along topographically-driven hydrological gradients. Tree stem growth is driven by the rainfall increase in the transition from dry to wet seasons, and not by greater irradiation or greater amount of rainfall as recent studies have suggested. Moreover, the most favorable conditions for growth move across the landscape along time, in association with topography, tracking the best conditions of soil-water availability. Valleys around terra-firme streams may benefit from some level of drought, therefore if dry-seasons become longer, the balance of growth may shift in favor of these areas. This would mean a lower net effect of droughts over the landscape than expected from drought experiments, which were conducted in upland areas far from places with a superficial water-table.
Keywords: Madeira; Topografia; Densidade da madeira